255 Leucine Supplementation During Continuous Feeding Enhances Lean Growth in a Preterm Piglet Model. (21st September 2022) - Posey, Erin A; Suryawan, Agus; Nguyen, Hanh; Stoll, Barbara; Sciarrillo, Christina; Vonderohe, Caitlin; Burrin, Douglas G; Fiorotto, Marta L; Davis, Teresa A
Abstract: Extrauterine growth restriction is a common complication of preterm birth and is associated with reduced lean growth and long-term morbidities. We previously showed that intermittent pulses of leucine during continuous orogastric feeding increases mTORC1 signaling to protein synthesis in skeletal muscle of neonatal pigs born at term. The objective of this study was to determine the extent to which leucine pulses during continuous feeding would promote lean growth by enhancing mTORC1 signaling in a preterm piglet model. Pigs delivered by cesarean section at 105 d gestation were continuously fed a protein and energy balanced milk-replacer diet [195 kcal ME and 13.5 g protein (kg body weight; BW) -1 ·d -1 )]. Pigs (n=11-12) were randomly assigned to Leucine (LEU) or Alanine (ALA, isonitrogenous control) groups and treatments were administered as a pulse (1.6 mmol·kg BW -1 ·h -1 ) for 1 h every 4 h for 21 d. Body composition was determined by DXA and indices of amino acid signaling and mTORC1 activation were determined postprandially, 60 min after initiation of the last pulse. LEU pigs had a 10% greater average daily gain (ADG) (P < 0.05) than ALA pigs. Total lean mass tended to be greater (+13%; P < 0.06) in LEU compared with ALA, and longissimus dorsi muscle weight was 17% heavier in LEU than ALA pigs (P=0.01). Indices of mTORC1 activation, i.e., phosphorylation of S6K1 and 4EBP1 and abundance of the eIF4E-eIF4G complex, were increased in longissimus dorsi and gastrocnemius muscle of LEU compared with ALA pigs (P < 0.05). These results show that leucine supplementation during continuous feeding enhances mTORC1-activated translation initiation in skeletal muscle leading to an increase in muscle mass and lean growth in a preterm piglet model. Research was supported by NIH and USDA.